Identificação e caracterização de elementos transponíveis em Sporothrix schenckii e S. brasiliensis - Fernanda Lourenço Alves Gonzaga (2017)
Transposable elements (TEs) are mobile genetic elements classified into retrotransposons (class I) and DNA transposons (class II). With the sequencing in Brazil of two strains of Sporothrix spp. (S. schenckii MYA-4821 and S. brasiliensis MYA-4823), it was possible to start the study of transposable elements, contributing to the first publication of these genomes in 2014. By several strategies and bioinformatics tools, we identified, classified and named 54 TEs belonging to 4 different orders and 6 superfamilies. Most identified TEs are truncated and defective, with the exception of RELTHRIX from LINE order, a TE only identified in S. schenckii. Retrotransposons were prevalent in both genomes, belonging to orders LTR and LINE. S. brasiliensis genome has twice the TE amount (0.6% of the genome) if compared to S. schenckii (0.3% of the genome) and this increase is due to expansion of SbGYP8 of Gypsy superfamily. From the 54 TEs, 25 had in silico evidences to be exclusive of S. schenckii, 23 from S. brasiliensis, while 6 were shared by both genomes. Experimental validation of the in silico data was done by PCR with primers to conserved TEs domains. The majority of TEs were considered to be potential markers to S. schenckii or S. brasiliensis since have been amplified exclusively in one of the genomes. Thus, 16 of them were tested as markers in 29 isolates of different species of Sporothrix spp. Four TEs (SbhAT1, SbMULE1, SbGYP8 and SbLINE1) showed good results, amplifying in most S. brasiliensis isolates tested (although they were amplified in S. schenckii Ss02). Fourteen TEs and their copies were analyzed phylogenetically, corroborating bioinformatics and PCR data. Phylogenetic analyzes indicated that the presence of some of the TEs in different species of Sporothrix spp. is probably due to the existence of these elements in a common ancestor of the genus. Thus, the presence of truncated copies observed in the transposable elements in S. schenckii MYA-4821 and S. brasiliensis MYA-4823 could be associated with a natural process of degradation of elements, considering that some of the TEs could be present since the divergence between species. The majority of elements have a low amount of cytosine-guanine and appear to have undergone the action of RIP, a defense mechanism against TEs. Genomic environment revealed that most TEs are found in clusters and about 56% of the proteins annotated close to the TEs are hypothetical or of yet unknown function. TEs were found close to proteins related to metabolic pathways and transport, in addition to serine/threonine kinases and transcription factors. The presence of TEs near genes encoding proteins of unknown function or genes related to virulence, creates the idea that these TEs may have been important for events of duplication and in the acquisition of new genes related to the adaptation to animal and human hosts. Therefore, a more detailed study of TEs, now identified and classified in the genomes of S. schenckii and S. brasiliensis, could point a direction in a possible role in the pathogenicity and adaptation of the fungus to its hosts.